2010
DOI: 10.5012/bkcs.2010.31.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Idarubicin Analogues Containing a Glucose or Galactose Moiety as a Glycone

Abstract: The new idarubicin analogues (12 and 13) with a glucose or galactoseas as a glycone were synthesized from daunomycin (2). (+)-4-Demethoxydaunomycinone (6) obtained from reaction of 2 with AlCl3 was converted to 4-trifluoromethanesulfonyl daunomycinone (7) through reaction with trifluoromethanesulfonic anhydride. The treatment of 7 with 1,1-bis-(diphenylphospino)ferrocene/Pd(OAc)2 in triethylamine/formic acid/dioxane provided the idarubicinone (5b). Glycosylation of 7-hydroxy group of 5b with two kinds of tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Efforts are therefore on to find out new but cheaper analogues and derivatives of anthracycline drugs. In several studies [11][12][13][14][15][16] we were able to show that much cheaper hydroxy-9, 10-anthraquinones mimic the behavior of anthracycline drugs. A very recent study by Rossi et al 17 showed that 1, 4-dihydroxy-9, 10-anthraquinone and 1, 8-dihydroxy-9,10-anthraquinone have promising anticancer activity though they do not posses any sugar moiety.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Efforts are therefore on to find out new but cheaper analogues and derivatives of anthracycline drugs. In several studies [11][12][13][14][15][16] we were able to show that much cheaper hydroxy-9, 10-anthraquinones mimic the behavior of anthracycline drugs. A very recent study by Rossi et al 17 showed that 1, 4-dihydroxy-9, 10-anthraquinone and 1, 8-dihydroxy-9,10-anthraquinone have promising anticancer activity though they do not posses any sugar moiety.…”
mentioning
confidence: 94%
“…Although several studies on hydroxy-9, 10-anthraquinones [11][12][13][14][15][16] and mitoxantrone (an amino hydroxy-9, 10-anthraquinone) [18][19][20][21][22] were extensively carried out the other amino hydroxy-9,10-anthraquinones have not been seriously investigated as a possible substitute of anthracycline anticancer drugs.…”
mentioning
confidence: 99%
“…Therefore, efforts are presently afoot to evaluate new but comparatively less expensive substitutes of the known forms of these drugs. Through several studies [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , we and others were able to develop less expensive hydroxy-anthraquinone-mimetic drugs. Rossi and coworkers [17] showed that two variant hydroxy-anthraquinones that do not posses any sugar moiety to exhibit significant chemotherapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on anthracyclines and their metal complexes mention their interaction with DNA either in vitro or in vivo. [5][6][7][8][9][10][11] Although there are many applications of anthracyclines in chemotherapy, these drugs, being very costly, may find a hindrance to their use in patients of economically challenged countries. This is most unfortunate and needs serious consideration.…”
Section: Introductionmentioning
confidence: 99%
“…20 Mitoxantrone induces compaction of isolated chromatin 21 and protein-associated DNA cleavage 22 and inhibits DNA and RNA synthesis. Although studies on hydroxy-9,10-anthraquinones [11][12][13][14][15][16][17][18] and mitoxantrone [19][20][21][22][23][24] have been extensively carried out, amino-hydroxy-9,10-anthraquinones have not yet been seriously investigated as a possible substitute and hence the present study has been carried out on 1-amino-4-hydroxy-9,10-anthraquinone.…”
Section: Introductionmentioning
confidence: 99%